Effects of metals on seed germination, root elongation, and Coleoptile and hypocotyl growth in Triticum aestivum and Cucumis sativus - Munzuroglu, O; Geckil, H (Springer-Verlag, 2002)
A simple, fast, and easy-to-perform method was carried out for the quantification of the inhibitory effects of metals on wheat and cucumber. The method uses seed germination, root elongation, and hypocotyl and coleoptile growth in these plants as parameters in the presence of varying concentrations of metals. Metals selected for this study were Hg, Cd, Co, Cu, Pb, and Zn. Although effective concentrations of these metals for a certain degree of inhibition were different, both plants had a reduced seed germination rate, root, and hypocotyl or coleoptile length with increasing concentrations. Mercury was determined to be the most inhibitory metal on these parameters. This metal caused a complete inhibition of germination in wheat and cucumber seeds at certain concentrations-greater than or equal to1.5 mM in cucumber and at 1.7 mM in wheat. No other metal caused this kind of inhibition even at the highest concentration (8.0 mM) applied. Though this metal possessed a higher inhibition of germination in cucumber than in wheat seeds, the inhibitory effects of other metals used were the reverse, being higher in wheat. With some exceptions, all metals in selected concentrations caused a significant (p < 0.01 or p < 0.05) decrease in germination rate of both plants compared to control group seeds.
Keywords: Cadmium; Wheat; Lead; Seedlings; Toxicity; Mercury; Cobalt; Stress; Nickel; Zinc